The natural HLA-Peptidome of Sezary Syndrome: uncovering antigens for T cell-based immunotherapy - Nyambura, Lydon; Textoris-Taube, Kathrin; Walden, Peter (Journal of Medical Science, 2025)
Introduction. Sezary syndrome (SS) is a rare and aggressive form of cutaneous T-cell lymphoma, that has a poor prognosis, with a median overall survival time of less than 3 years. Despite advances in its treatment, SS is a challenge to manage, often characterized by high rates of relapse and limited response to therapy in many patients. The main challenge for treatment, including vaccine development is its heterogeneity. In its molecular and genetic characteristics, clinical presentation, disease progression, and treatment response. Understanding the SS heterogeneity at the omics level is vital in developing T-cell mediated immunotherapeutic. Material and methods. In this study naturally presented human leukocyte antigen class I (HLA-I) peptides were isolated from SS patients leukophoresis samples and analyzed using high performance liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS), and source proteins evaluated for immunotherapy application. Results. The total number of HLA-I–restricted peptides and source proteins identified in SS leukophoresis patient samples was about the same, and they were heterogeneous and individualized. Only a small fraction of HLA-I peptides and source proteins was found to be shared between and among the patients. Peptide lengths were dominated by nanopeptides, with preferred processing by chymotrypsin. The source proteins were predominantly from the cytoplasm, and primarily involved in biosynthesis and regulation. Furthermore, the HLA-I peptides were presented from proteins of top 20 genes with somatic mutations in SS that include NCOR1, TRRAP, JAK3, PLCG1, TP53 and STAT3 (SS associated antigens - SAAs). These SAAs had varying mutation types and frequencies- dominated by missense variant, allele-dependent immunogenicity- highest in HLA-A*11:01 and HLA-A*02:01 and lowest for HLA-A*01:01-with TRRAP showing high affinity peptides, low gene expression levels in normal tissue (except STAT3), significant protein interaction network- including JAK3 and STAT3 at primary level. Conclusions. This study findings, contributes to the overall understanding SS HLA-I peptidome landscape, and highlights potential T-cell mediated immunotherapeutic targets.